Rehabilitation of Vertical Dimension Decreased Cases in Elderly Patients - Adrian, Nova (Indonesian Dental Association, 2019)
Introduction: An elderly person is considered elderly when he or she reaches 60 years or more. Among the problems that occur in the elderly is the loss of teeth. Elderly patients who lose several teeth might decrease the vertical dimension; additional tooth migration causes extensive loss contact. Obtaining an ideal occlusal schema was challenging for dental practitioners. A suitable and efficient preprosthetic plan might be essential to acquire comfortable and good dentures for patients. Our objective is to organize a suitable and efficient preprosthetic, planning to acquire comfortable for patient. Case Report: A 69 year old man who had lost several teeth due to caries on teeth 15, 14, 13, 12, 11, 21, 24, 25, 26, 34, 37, 44, 46 and 47. He had used dentures over the last 15 years and needed a new one because the previous dentures was impaired. We determined the tentative vertical dimension and position to the articulator. Preprosthetic planning fixed the prosthesis on 36 and 27 with extraction on 18. A second impression was made and placed on the articulator, arranging the teeth and try in wax dentures continously. We used a definitive dentures and suggest a periodic control. Conclusion: The loss of several teeth decreased vertical dimensions, and existing tooth migration caused extensive loss contact. The systematic preprosthetic planning might be arranged on behalf of success prosthesis.